2009
DOI: 10.1159/000257432
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Induces MAPK Signaling in Neural Progenitors without Alleviating Glucocorticoid-Induced Inhibition of in vitro Neurogenesis

Abstract: We recently demonstrated that prolactin (PRL) prevents chronic stress-induced inhibition of adult hippocampal neurogenesis. It remained unsettled, however, whether PRL is acting directly on neural stem and progenitors cells (NPCs) or if neurogenesis is affected by an indirect mechanism, for example through the extensively described effects of PRL on the HPA axis. To address this point, we used neurosphere cultures derived from the adult rat hippocampus as an in vitro model for NPCs. Dexamethasone (DEX) was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(59 reference statements)
0
9
2
Order By: Relevance
“…In contrast, the study by Torner and colleagues observed no effect of direct PRL administration on hippocampal precursor proliferation [12]; possibly due to different delivery methodology (subcutaneous injections rather than intracerebroventricular infusion) or dosage and timing of PRL administration. Also, and in contrast to our findings, an in vitro follow-up study published by the same group demonstrated that PRL doesn’t affect cell proliferation, differentiation or survival of NPCs using the neurosphere assay [23]. This led to their conclusion that the effect of PRL observed in vivo is probably not due to a direct effect of PRL on NPCs, but rather via an indirect mechanism such as PRL-induced attenuation of the HPA axis response [23].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, the study by Torner and colleagues observed no effect of direct PRL administration on hippocampal precursor proliferation [12]; possibly due to different delivery methodology (subcutaneous injections rather than intracerebroventricular infusion) or dosage and timing of PRL administration. Also, and in contrast to our findings, an in vitro follow-up study published by the same group demonstrated that PRL doesn’t affect cell proliferation, differentiation or survival of NPCs using the neurosphere assay [23]. This led to their conclusion that the effect of PRL observed in vivo is probably not due to a direct effect of PRL on NPCs, but rather via an indirect mechanism such as PRL-induced attenuation of the HPA axis response [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, and in contrast to our findings, an in vitro follow-up study published by the same group demonstrated that PRL doesn’t affect cell proliferation, differentiation or survival of NPCs using the neurosphere assay [23]. This led to their conclusion that the effect of PRL observed in vivo is probably not due to a direct effect of PRL on NPCs, but rather via an indirect mechanism such as PRL-induced attenuation of the HPA axis response [23]. In that study, the concentration of PRL used in vitro was between 10 and 1000 ng/mL, which is between 10 and 1000 times that used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, Dex induction of Gjb6 in our neurosphere cultures may be reflective of GR action in astrocyte progenitor cells. Gbx2 is a homeobox transcriptional factor that has been shown to regulate various aspects of neural stem cell differentiation (44) and may contribute to the reported effects of GCs on differentiation of distinct neuroprogenitors (11)(12)(13). No role for phospholipase C-related protein (Plcl2) in neurodevelopment or GC action has been reported, although Plcl2 was identified in exome sequencing analysis as one of 40 genes with protein coding sequence variations in schizophrenia patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse cerebellum, neonatal treatment with Dex increased apoptosis of the neural progenitor cells within the extra granule cell layer and decreased overall numbers of internal granule layer neurons (10). GC effects on the differentiation of NPSCs are varied and conflicting; reduced differentiation of glial cells by GCs was reported in mesencephalic NPSCs and adult rat hippocampal progenitor cells, while GCs increased the differentiation of glia in human NPSC cultures (11)(12)(13). GC responses are mediated primarily by the glucocorticoid receptor (GR), a member of the nuclear receptor superfamily of transcription factors (1,14), through the actions of two separate but interrelated mechanisms.…”
mentioning
confidence: 99%
“…Prolactin is a regulator of the stress response and stimulator of neurogenesis in the subventricular zone, but also protects neurogenesis in the dentate gyrus of chronically stressed mice and promotes neuronal fate (Torner et al 2009). Neural stem and progenitors cells express the prolactin receptor and prolactin signals in these cells via ERK 1/2, however in vitro studies did not observe any effect of prolactin on these neural precursors proliferation, differentiation or survival, suggesting that prolactin action on in vivo neurogenesis occurs via an indirect mechanism (Wagner et al 2009). The effects of growth hormone on adult neurogenesis will be widely analyzed later in this chapter.…”
Section: Pituitary Hormones and Adult Neurogenesismentioning
confidence: 99%